If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (8x + 3x + -2) + -1(8x + 4) = 9 Reorder the terms: (-2 + 8x + 3x) + -1(8x + 4) = 9 Combine like terms: 8x + 3x = 11x (-2 + 11x) + -1(8x + 4) = 9 Remove parenthesis around (-2 + 11x) -2 + 11x + -1(8x + 4) = 9 Reorder the terms: -2 + 11x + -1(4 + 8x) = 9 -2 + 11x + (4 * -1 + 8x * -1) = 9 -2 + 11x + (-4 + -8x) = 9 Reorder the terms: -2 + -4 + 11x + -8x = 9 Combine like terms: -2 + -4 = -6 -6 + 11x + -8x = 9 Combine like terms: 11x + -8x = 3x -6 + 3x = 9 Solving -6 + 3x = 9 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + 3x = 9 + 6 Combine like terms: -6 + 6 = 0 0 + 3x = 9 + 6 3x = 9 + 6 Combine like terms: 9 + 6 = 15 3x = 15 Divide each side by '3'. x = 5 Simplifying x = 5
| -0.5(6b+8)+5b=6(1-b)-2 | | 11-9x=47-16x | | (10x+8x-3)-(10x+7)=30 | | 8+6r-2=9r+11-2r | | 114-5x=22x+15 | | (19t-13)+(-6t+5)= | | 1-10w=81 | | 5(y+7)=-35(y-1)-40 | | 5x-3=(x+7)+3x | | 2x+12=-87-9x | | 106-6x=2x+18 | | (g-9)5= | | -30-6x=10-10x | | 49-4x=7x+16 | | -7x+8=15 | | -(3y+3)-(-2y-8)=1 | | 7(x-2)=-5(x+3)+22 | | 6(3x-5)=3(6x+9) | | 3mp+-mp= | | 15x+14-2x=3x-3 | | 4+16y-3=8y+34-3y | | 7+3m=-26 | | -6x+9=45 | | 24=-4(x-4)+9(x-3) | | m-1-m+3= | | 7s+7s=98 | | 8(y-3)+4(y+1)=28 | | -8.1x=32.4 | | 2(x-17)=-2 | | -9.5x=19.0 | | 6t=-75 | | 0=-(x-3) |